A finite element study of stresses developed in plastic encapsulated electronic packages during leadframe pull-out testing - Ng, Shioo Wat. (2008)
The objective of this project is to simulate the stresses developed in the epoxy encapsulated dummy integrated circuit package during leadframe pull-out testing. Finite element analyses are utilized to simulate the stresses developed due to free and constrained displacement boundary conditions, the change in profile of the epoxy encapsulation, and the change in modulus of elasticity of the lead-frames. The numerical results showed that displacement boundary conditions had a greater effect on the stress field in the IC package, which resulted in two distinctively different stress fields in the package. On the other hand, the change in the profile of the epoxy encapsulation and the modulus of elasticity of the lead-frame did not produce significantly different stress fields in the package respectively, but caused some differences in the magnitude of the stresses, ranging from 1 to 44%.